Immediate effects of kinematic taping on lower extremity muscle tone and stiffness in flexible flat feet - Wang, Joong-San (J Phys Ther Sci, 2016)
[Purpose] This study aimed to examine the immediate effects of kinematic taping on the tone and stiffness in the leg muscles of subjects with flexible flat feet. [Subjects and Methods] A total of 30 subjects, 15 in the kinematic taping and 15 in the sham taping group, were administered respective taping interventions. Subsequently, the foot pressure and the tone and stiffness in the tibialis anterior, rectus femoris, medial gastrocnemius, and the long head of the biceps femoris muscles of both the lower extremities were measured. [Results] The foot pressure of the dominant leg significantly decreased in the kinematic taping group. The muscle tone and stiffness in the rectus femoris muscle of the dominant and non-dominant leg, tibialis anterior muscle of the dominant leg, medial gastrocnemius muscle of the non-dominant leg, and the stiffness in the dominant leg significantly decreased. The muscle tone and stiffness generally increased in the sham taping group. However, no significant difference was observed between the 2 groups. [Conclusion] This study demonstrated that kinematic taping on flexible flat feet had positive effects of immediately reducing the abnormally increased foot pressure and the tone and stiffness in the lower extremity muscles.